Selective depressive effect of pectin on sphalerite flotation and its mechanisms of adsorption onto galena and sphalerite surfaces. (15th August 2021) - Wang, Changtao; Liu, Runqing; Sun, Wei; Jing, Nianwen; Xie, Feifei; He, Qilin Zhai Dongdong
Highlights: Sphalerite was selectively depressed using pectin as depressant in galena flotation. Pectin chemisorbed on sphalerite through carboxyl and hydroxyl groups. Zn atoms on sphalerite surface function as adsorption sites. Pectin weakly adsorbed on galena surface through hydrophobic interaction. Abstract: In this work, pectin was investigated as a non-toxic and eco-friendly sphalerite depressant in the flotation separation of galena and sphalerite. The selective adsorption of pectin on sphalerite surfaces was predicted by molecular dynamics simulations, and its depressive effect was evaluated by single- and mixed-mineral flotation tests. The relevant adsorption characteristics and associated interaction mechanisms were further investigated by electrokinetic studies, adsorption density analysis, Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). The flotation results demonstrated that pectin exerts a selective depressive effect on sphalerite flotation and could achieve the separation of galena from sphalerite. Electrokinetic and adsorption studies confirmed that pectin is adsorbed on both mineral surfaces. However, pectin is adsorbed much less extensively on the galena surface than on the sphalerite surface and could be displaced by xanthate. FTIR and XPS results revealed that the interactions between pectin and galena are physical interactions, the most likely of which is hydrophobic interactions based on the "salting-out" effect. The strong adsorption of pectin on the sphalerite surface was attributed to chemical complexation, and it could not be displaced by xanthate through competitive adsorption. Specifically, pectin is chemisorbed on the sphalerite surface through the O atoms of its –OH and –COOH groups, while Zn atoms on the sphalerite crystals function as adsorption sites.